2010
DOI: 10.1021/cg101002x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Study of Salicylic Acid Salts of a Series of Azacycles and Azacrown Ethers

Abstract: Interaction of salicylic acid (saH) with the azacycles piperidine (pipe) and meso-5,7,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane (teta) and with the aza-crown ethers aza-12-crown-4 (A12C4), benzoaza-15-crown-5 (BA15C5), aza-18-crown-6 (A18C6), and diaza-18-crown-6 (DA18C6) afforded the proton-transfer complexes (organic salts)whose structures were determined by a single crystal X-ray method. These products were also obtained by the same synthetic conditions starting from acetylsalicylic acid (asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 89 publications
2
3
0
Order By: Relevance
“…In support of recent studies, , we have shown the reoccurrence of the pyridinium-carboxylate and 2-amino­pyridinium-carboxylate robust heterosynthons in organic salts produced by co-crystallization of mono- and diamino­pyridines with aliphatic dicarboxylic acids. , On the other hand, the reoccurrence of the stacking motifs in the presence of strong charge-assisted NH + ···O­(COO – ) hydrogen bonds has been shown by some of us taken as the examples two systems, NSAID drug mefenamic acid-cyclic (acyclic) amine, and salicylic acid-cyclic amine (azacrown-ether). , …”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…In support of recent studies, , we have shown the reoccurrence of the pyridinium-carboxylate and 2-amino­pyridinium-carboxylate robust heterosynthons in organic salts produced by co-crystallization of mono- and diamino­pyridines with aliphatic dicarboxylic acids. , On the other hand, the reoccurrence of the stacking motifs in the presence of strong charge-assisted NH + ···O­(COO – ) hydrogen bonds has been shown by some of us taken as the examples two systems, NSAID drug mefenamic acid-cyclic (acyclic) amine, and salicylic acid-cyclic amine (azacrown-ether). , …”
Section: Introductionsupporting
confidence: 79%
“…53,54 On the other hand, the reoccurrence of the stacking motifs in the presence of strong charge-assisted NH + •••O(COO − ) hydrogen bonds has been shown by some of us taken as the examples two systems, NSAID drug mefenamic acid-cyclic (acyclic) amine, and salicylic acid-cyclic amine (azacrown-ether). 55,56 In this study, we present the crystal structures of adducts obtained by co-crystallization of three N-heterocyclic drug molecules, niacin (NIA = pyridine-3-carboxylic acid), allopurinol (ALP = pyrazolo (3,4-d)pyrimidin-4-one), and amiloride (AMI = 3,5-diamino-6-chloro-pyrazine-2-carbonyl)-guanidine), with the same coformer, amphoteric 2,4-pyridinedicarboxylic acid (PDA, Scheme 1). All drug molecules and coformer have several binding sites of different acidity/basicity capable of participating in hydrogen-bonding systems and proton transfer, while their planar skeletons are predisposed for potential stacking interactions in these systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This journal is © The Royal Society of Chemistry 2023 acetylsalicylic acid into salicylic acid in solution, as a similar behaviour has already been reported for similar systems. 38 The proton and carbon NMR spectra of 5 and 6 are similar to those obtained for compounds 3 and 4. The similarity of the NMR spectra of the ionic cocrystal 5 with those obtained for the salts 3, 4 and 6 might be due to the fact that in a D 2 O/ (CD 3 ) 2 SO solution, hydrogen bonds between cations and anions are broken.…”
Section: Crystengcomm Papersupporting
confidence: 62%
“…The crystal structure of triethylammonium benzoate salt is similar to that of its analogue salicylic salts [1,2]. Among the complex intermolecular interactions [3,4], the most important hydrogen bonding is N1-H1×××O2 (bond length 2.744 (2) .I na ddition, the hydrogen bonds O4-H4D×××O2 and O3-H3B×××O1 (bond lengths 2.58(2) Åa nd 2.68(2) Åand bond angles 163.25°and 162.4°, respectively) are another important force to stabilize the crystal structure [5].…”
Section: Discussionmentioning
confidence: 82%
“…The crystal structure of triethylammonium benzoate salt is similar to that of its analogue salicylic salts [1,2]. Among the complex intermolecular interactions [3,4], the most important hydrogen bonding is N1-H1×××O2 (bond length 2.744(2) Å; bond angle 174.4°), providing the main driving force for direct binding of carboxylate anion [3,5- …”
Section: Discussionmentioning
confidence: 99%